Recensiones - Martín-Baró, Ignacio; Montes, Segundo; lbisate, F. J.; Gondra, J. M.; Ungo, Guillermo Manuel (ECA: Estudios Centroamericanos, 1975)
No hay resúmenes disponibles.ECA Estudios Centroamericanos, Vol. 30, No. 326, 1975: 761-769.